Corrigendum to Post-kinematic lithospheric delamination of the Wuyi-Yunkai orogen in South China: Evidence from ca. 435 Ma high-Mg basalts (vol 154, pg 115,2012) - Yao, W.; Li, Zheng-Xiang; Li, W.; Wang, X.; Li, X.; Yang, J. (ELSEVIER SCIENCE BV, 2014)
There is an error in Table 1 of the published article